2022
DOI: 10.1037/dev0001284
|View full text |Cite
|
Sign up to set email alerts
|

Long-term benefits after a rhyme-repetition based intervention program for kindergarteners: Better reading and spelling in the first grade.

Abstract: Oral language proficiency in kindergarten can facilitate the acquisition of reading and writing. However, in diglossic languages, like Arabic, the large gap between the spoken and the formal, modern standard (MSA) varieties of the language may restrict the benefits of oral language proficiency to subsequent literacy skills. Here, we tested, in a randomized controlled study, whether an intervention program, implemented in kindergarten, that familiarized the children with rhymes presented in MSA through recitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 137 publications
(237 reference statements)
0
3
0
Order By: Relevance
“…Building vocabulary is also one of the focuses of this approach. Hence, giving importance and meaning to the reading materials (Eghbaria et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building vocabulary is also one of the focuses of this approach. Hence, giving importance and meaning to the reading materials (Eghbaria et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, recent studies suggest that children's processing of songs may not be limited to a shallow encoding of verbal material. Several studies showed that structured interventions where Arabic-speaking kindergarteners recited or listened to nursery rhymes successfully improved their aptitude in Modern Standard Arabic, in domains such as vocabulary, listening comprehension, and reading (Eghbaria-Ghanamah et al, 2020, 2022. Moreover, Eghbaria-Ghanamah et al (2021) found that children retained the content of nursery rhymes 6 months after intervention, even when they could not recall the rhymes verbatim.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Children's nursery rhyme experiences have been associated positively with phonological and literacy skills (see Dunst et al, 2011 for a review). Furthermore, recent experimental studies found that interventions where Arabic-speaking kindergarteners recited or listened to nursery rhymes improved their aptitude in Modern Standard Arabic (i.e., literary language used in most Arabic speaking societies), in domains such as vocabulary, listening comprehension, and reading (Eghbaria-Ghanamah et al, 2020, 2022. The benefits of children's songs certainly should not be limited to language and literacy development, considering the diverse educational content often included in children's songs.…”
mentioning
confidence: 99%